The Impact of Carbon Disclosure Level on Cost of Capital in China - Chen, Tianyu (2022)
This paper focuses on the relationship between the level of disclosure of carbon information and the cost of capital. Firstly, it reviews the literature, defines the relevant concepts, and theoretically analyses the impact of the level of carbon information disclosure on the cost of capital. The current situation and problems of carbon information disclosure level of Chinese enterprises were analyzed before the empirical study. Based on the consideration of Chinese national conditions and the current situation of carbon information disclosure level, instead of using CDP scores with low participation of Chinese enterprises, the carbon information disclosure quality evaluation system applicable to China was applied to measure the carbon information disclosure level. This paper empirically examines the impact of the level of carbon information disclosure on the cost of equity and debt capital by building a multiple regression model using a sample of 885 companies listed on A-shares from 2015 to 2020 that have published social responsibility reports that include environmental information or environmental reports. The results of the study show that the level of carbon information disclosure by Chinese enterprises is still low. The level of carbon disclosure can be significantly negatively related to the cost of equity capital and positively related to the cost of debt capital. The findings of this paper provide empirical evidence on the usefulness of improving the level of carbon information disclosure, which can enhance the intrinsic drive of Chinese companies to disclose carbon information. This provides a reference for the development of a carbon information disclosure system in China, as well as a basis for stakeholders to use the carbon information disclosed by enterprises to make reasonable decisions and further promote the development of a low-carbon economy in China.